Comparative pharmacokinetics of cefotaxime in normal cyclic and endometritis affected buffaloes - Singh, Satinderpal; Gandotra, V K; Sharma, S K; Srivastava, A K (The Indian Journal of Animal Sciences, 2005)
The pharmaeokinetics and dosage regimen of cefotaxime were investigated in normal cyclic and endometritis affected buffaloes (6 each). Cefotaxime was administered @10mg.kg-1 b.wt by intramuscular injection in all animals. In normal cyclic buffaloes, peak concentration of cefotaxime reached was 8.16±0.04 µ.mlÂ¯Â¹ at 15 min and the drug was detected up to 8 hr, while in endometritis affected buffaloes,the plasma levels were significantly lower than the normal cyclic buffaloes, but the drug was detected up to 12 hr. In normal cyclic buffaloes, the absorption half-life, elimination half-life volume of distribution and MRT (mean rersidence time) values were 0.85±0.27 hr, 187±0.08 hr,1.62±0.04 L.kgÂ¯Â¹ and 2.83±0.12 hr respectively, while in endomitritis affected buffaloes, the corresponding values was 0.19±0.05 h,5.12±0.78 hr, 3.24±0.38L.kgÂ¯Â¹ and 7.49±1.10 hr, respectively. Uterine concentration of cefotaxime was comparativelymore in endometritis affected buffaloes than normal cycling buffaloes. To maintain a minimum therapeutic concentration of 1 µg.kgÂ¯Â¹ b.wt..a satisfactory dosage regimen of cefotaxime in endometritis affected buffaloes was 12 mg.kgÂ¯Â¹ followed by 8.5 mg.kgÂ¯Â¹ at 8hr intervals.